A novel application of vacuum preloading: conception, analysis and performance evaluation. Issue 1 (18th February 2022) - de Lillis, Armando; Fasano, Gianluca; Flora, Alessandro; Miliziano, Salvatore
Abstract : The paper presents an original application of vacuum preloading, conceived for the reclamation of containment facilities hydraulically filled with fine-grained sediments, and the evaluation of its performance. The technique, which consists in the installation of horizontal vacuum layers within the dredged soil mass, with the aim of reducing the soil volume and accelerating the consolidation while filling is underway, was successfully implemented for the first time in the port of Gaeta (Italy). The construction sequence and the numerical models developed to analyse the huge changes of state experienced by the soil – whose prediction is paramount in evaluating the actual storage capacity of the impoundments – are described. Monitoring data and in situ test results are illustrated and compared with numerical predictions (class A, C and back-analyses), confirming the effectiveness of the technique and of the modelling choices. Finally, the lessons learned from the case history to optimise the use of the technical solution and of the modelling approach are reported. The presented vacuum preloading technique and analysis methods can be highly beneficial to the environmentally sound and cost-effective design of reclamation works, especially, but not only, those involving undersized containment facilities.